Impact assessment of Iran's health technology assessment programme - Bahareh Yazdizadeh; Farideh Mohtasham; Ashraf Velayati (BMC, 2018)
Abstract Background Following approximately 10 years from the beginning of Iran's national Health Technology Assessment (HTA) programme, the present study aims to evaluate its success by examining the impact of HTA and identifying the determinant factors leading to the implementation of HTA report results. Methods The triangulation method was employed herein. HTA reports were initially identified and their impact and determinant factors were then examined from the perspectives of both researchers (by preparing a questionnaire according to the Payback model and sending it to HTA principle investigators) and stakeholders (semi-structured interviews held with each HTA stakeholder). Simultaneously, the quality of the HTA reports was examined with relevant critical appraisal checklists. Results The impact of 19 equipment technologies and four pharmaceutical technologies were assessed in this study. Twenty researchers replied (response rate, 86.96%) to the questionnaire on the impact of HTA reports from the researcher's perspective. To assess the impact of HTA reports from the stakeholder's perspective, seven policy-makers were chosen and interviewed as the main target audience. The most common step taken to disseminate the results of the HTA projects was publication. Conducting the HTA had taught researchers and their colleagues' new skills and had facilitated the securing of research grants from other organisations. Most reports had used the systematic review method but the relevant details had been scarcely presented regarding outcomes, costs and analysis. The greatest impact of HTA reports on decision-making had been on policy-makers providing and allocating finances. Barriers in stewardship, identification and prioritisation of topics, performance and dissemination of HTA results were the main barriers of implementing HTAs. Conclusions In most aspects, the status of HTA impact reports need improvement. Thus far, the barriers and facilitators of the HTA programme in Iran have been investigated in other studies. These findings should be pooled to reach a solution that can be actively applied to the health system to improve the status quo of HTA in Iran.